Heteropolysaccharide of KGM-xanthan hydrogels for the removal of bacteria in a wound model - Shahbuddin, Munira; Ahmad Raus, Raha; Yusof, Aqilah; Mahamad, Siti Syazwani (IIUM Press, 2022)
This project focused on developing polysaccharides hydrogels from Konjac Glucomannan (KGM) and Xanthan gum in removing the bacterial load on the wound. This new therapy design is due to the traditional wound care methods using antibiotics and normal hydrogel, which cannot adequately treat biofilm infected woundsin the healing process. For the treatment of bacterial infected wound, bacterial removal need to be done physically and manually by debridement, which is very painful and require the use of general anesthesia. Therefore, to reduce the formation of slough and necrotic tissue by the formation of bacterial biofilm, there is a need for specific hydrogels that will be able to remove bacteria from the wounded site to prevent further infection and to enhance the healing process. This study focused on the design and optimization of polysaccharide based hydrogels for the wound treatment. Polysaccharide based hydrogels from Konjac Glucomannan (KGM) and Xanthan gum were developed at different ratios to optimize the physical and chemical properties of the hydrogel that relate to the effectiveness of bacterial removal. Film casting technique was used in the development of the hydrogel film. Konjac Glucomannan (KGM) and Xanthan gum were selected because of their natural polymer properties which are non–toxic, biocompatible and safe to be used. The hydrogels weretested in vitro for bacterial removal efficacy, using E.coli species colonies cultured on a gel inside a petri dish to represent the condition of bacteria infested wound bed. Hydrogel with 50 : 50 % composition blend of KGM-XG was found to be the most effective in the removal of E.coli colonies with 13x103 CFU/mL at 95% water content. Morphological studies of hydrogels showed flat interfacial morphologies, except for the sample with 100% of Xanthan without KGM. The results present in this study suggested that the biological activities and adhesion of the hydrogels were not controlled only by the chemical structure but also by the composition of the compound and the amount of water present in the hydrogels.